MEMBUMIKAN AL- QURAN PANCASILA DAN ETOS SAINS - Miranda Yulia Alfiani (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
The pleasure of paradise also hill in general are human busy with himself never thought of the life of the hereafter and continuous, breaking the law moral obligation for the country to establish a security system social where a who are religious namely by zakat play the role of central. Islam attention to the poor is evidence of the holy Quran expressed to the prophet verse, the vision for a leader is not just had to liberate the country but also must be to liberate welfare and prosperity humans are there in which, please help each other between fellow. Everyone who faithful in particular the prophet can adress syaithan temptations, the man who like this is the creation of God they beyond the angel God in the knowledge and in to spiritual, humans in the created on earth has a unique position, in give freedom wills, In order to be his mission of khalifah on earth, among mission is create a the social life on earth, social often connected with a man in society example the man who life in the village, the man who life in the city, it also there to do with a sense of emphaty, help of a rich to poor, help from powerful to a week, In a great line is classified into two things human relationship (verticals relation ship between human with God) (Horizontal relation ship between humans to humans) if it is good in yourself man, it can be certain someone that will also be good in the side of life, two it had become a benchmark in life, if the social already is well that it appears the life neat, is orderly and have a sense of symphaty and emphaty high. In this word there is no one big and no one little, there was only people who a great personal and a small personal, the purpose of the personality of inside the man could rich himself to be a good person, also able to rich people in the vicinity especially country that he occupy.